Development and validation of the reported outcome scale for patients with lumbar disc herniation - Chao Xu; Feng Huang; Shunxing Wang; Zhijun Tan; Haiyue Zhang; Zhe Yang; Ying Liang; Zhou Lu; Lei Shang (Annals of Medicine, 2025)
Objective The objective of this study was to develop a culturally relevant and clinically robust Patient-Reported Outcome (PRO) scale for patients with lumbar disc herniation (LDH), supporting standardized disease monitoring and quality of life assessment.Methods An initial 54-item pool was generated through literature review, patient interviews, and expert consultation. In the first round, 163 LDH patients were surveyed, and items were screened using exploratory factor analysis, critical ratio analysis, Cronbach's α, Pearson correlation, and discrete trend analysis. This yielded a 29-item trial scale. In the second round, 350 patients completed the scale for further refinement. In the third round, 539 patients were assessed for test–retest reliability and internal consistency. Validity was examined through content and criterion-related validity analyses.Results The final PRO scale comprised 29 items across five dimensions: Physical Symptoms (5), Physical Dysfunction (11), Psychological emotion (5), Social Adaptation (4), and Therapeutic Effect (4), explaining 69.07% of total variance. The overall Cronbach's α coefficient was 0.95, with subscale values between 0.81 and 0.94. Test–retest reliability was 0.85. Content validity was strong, with content validity ratios from 0.60 to 1.00 and content validity indices from 0.90 to 1.00. Criterion-related validity was supported by correlations of 0.74 with the Oswestry Disability Index and 0.62 with the Self-Rating Anxiety Scale.Conclusion The developed PRO scale is comprehensive, reliable, and valid for assessing the physical, psychological, and social impacts of LDH. It is well-suited for clinical use and quality of life evaluation in LDH patients.